FINANCIAL LITERACY, FINANCIAL SELF-EFFICACY, AND FINANCIAL WELL-BEING AMONG GENERATION Z: EVIDENCE FROM BATAM, INDONESIA - Eddo Nanda Oktarici; Alyssia Rahmadhani Dirmana Putri (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2026)
In the developing industrial regions, young adults like generation Z require more than just fundamental financial knowledge to navigate the complexities of the modern economic landscape, financial problems and financial freedom. This study analyzes the mediating role of financial self-efficacy in the relationship between financial literacy and financial well-being of Generation Z in Batam City Indonesia, a major economic hub in Indonesia. The primary data of the study were collected using the quantitative survey design method through purposive sampling of 350 Gen Z. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze the structural correlation between variables. The study results show that financial literacy directly and significantly affects financial self-efficacy and financial well-being. Moreover, financial self-efficacy significantly affects financial well-being while partially mediating the effect of financial literacy on financial well-being. This study reaffirms the importance of financial literacy; however, its effect is maximized when accompanied by self-confidence in managing finances. This study adds to the literature on the financial well-being of Generation Z and has practical implications for improving financial literacy and promoting self-efficacy towards sustainable financial conditions.